2011
DOI: 10.1002/csr.294
|View full text |Cite
|
Sign up to set email alerts
|

Doing Good Does Good? Sustainable Marketing of CSR and Consumer Evaluations

Abstract: This study focuses on the effect of the sustainable marketing of three types of corporate social responsibility (CSR) initiatives – sponsorship, cause‐related marketing, and philanthropy – on consumer evaluations with the moderating effect of psychological distance (social distance and spatial distance). Four hundred and eighty subjects participated in a 3x2x2 between‐subjects factorial design experiment. The results of the analyses were significant and in the direction hypothesized. Philanthropy was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 97 publications
(118 reference statements)
8
125
1
8
Order By: Relevance
“…Existent research found that diverse CSR activities positively influenced purchase behaviour when the product was perceived to be of high quality (Bhattacharya and Sen 2004) and that more positive attitudes towards a brand employing a CSR programme led to a stronger intention to maintain a relationship with that company, or to continue purchasing that brand (Darsono 2009, for CSR programmes in general). Similarly, in a recent study, Lii, Wu, and Ding (2013) demonstrated a strong relationship between positive attitudes and purchase intentions towards a product based on exposure to humane-oriented CSR information. Therefore, we hypothesize:…”
Section: Hypothesis 2b (H 2b)mentioning
confidence: 88%
See 2 more Smart Citations
“…Existent research found that diverse CSR activities positively influenced purchase behaviour when the product was perceived to be of high quality (Bhattacharya and Sen 2004) and that more positive attitudes towards a brand employing a CSR programme led to a stronger intention to maintain a relationship with that company, or to continue purchasing that brand (Darsono 2009, for CSR programmes in general). Similarly, in a recent study, Lii, Wu, and Ding (2013) demonstrated a strong relationship between positive attitudes and purchase intentions towards a product based on exposure to humane-oriented CSR information. Therefore, we hypothesize:…”
Section: Hypothesis 2b (H 2b)mentioning
confidence: 88%
“…One variable that likely affects consumers' responses to advertisements incorporating CSR appeals is the cultural dimension of humane orientation. If individuals in a given country see humane orientation as an important value, then the level of perceived humane orientation in an advertisement is expected to exert a stronger influence on the evaluation of that advertisement (see also Lii, Wu, and Ding 2013;Wang and Anderson 2011) as well as on the perception that the advertiser is a socially responsible corporation. The rationale here is that the greater the importance of humane orientation to the individual, the more central it becomes in the individual's evaluation of an advertisement.…”
Section: Individual and Country Differences In Responses To Humane-ormentioning
confidence: 98%
See 1 more Smart Citation
“…Li, Wu, and Ding [1] argue that, nowadays, the ultimate goal of corporate social responsibility (CSR) "is sustainability that not only incorporates, but also meets economic, social, and environmental responsibilities at the same time that they are linked to corporate success" (p. 16). In practice, to fulfill commitments to CSR and to sustainability, a company can carry out a variety of activities (CSR initiates) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Corporate Social Responsibility are believe to perceived a friendly and responsible image to the consumer, the role of marketing in CSR getting stronger; it had directed to two causes. First, it educates consumers on the firm good deed; second, it atttracts consumers using the marketing intention to draw consumers' good evaluation (Lii, Wu & Ding, 2013). If a consumer found out the good social responsibility of a firm by their own, they would most probably support the firm's action.…”
Section: Discussionmentioning
confidence: 99%